Current utilization and future prospects of emerging renewable energy applications in Canada - Islam, Mazharul; Fartaj, Amir; Ting, David S-K (Elsevier, 2004)
Canada has vast renewable energy resources due to its extensive geography and traditionally they have played an important role, particularly prior to the turn of the 20th century. Public interest in new renewable energy technologies (RETs) emerged and grew during the oil shocks of the 1970s and early 1980s. Even though many Canadian provinces had been deriving most of their electricity from hydroelectric power, the first oil crises of the 1970s ignited a strong interest in all forms of renewable energy. Though Canada has huge prospects for low-impact RETs, it is falling behind most industrialized nations in the expansion of these technologies due to a lack of supporting market structures and the absence of appropriate government policies and initiatives. This review focuses on only applications of low-impact emerging RETs that refer to wind, solar, small hydro, geothermal, marine and modern biomass energy. Today, these technologies are mostly in the dissemination, demonstration and early stage of commercialization phase in Canada and currently they contribute less than 1% of the total primary energy consumption. It is evident from the past experience of Europe and Japan that environmentally benign RETs can contribute significantly toward Canada's Kyoto target of reducing greenhouse gas emissions by displacing the use of conventional fossil fuels, and help Canada take an essential step toward a sustainable energy future. In this paper, the current energy utilization scenario of Canada has been analyzed and an array of emerging RET applications has been presented under the category of: (i) green power technologies; (ii) green heat technologies; and (iii) green fuel technologies. © 2003 Elsevier Ltd. All rights reserved.